DENTAL MARKETING: BENEFITS AND LIMITATIONS - Oprea-Valentin Busu; Cristina-Elena Andrei; Mihai-Narcis Popescu (Annals of the University of Craiova: Economic Sciences Series, 2020)
Compared to other medical sectors, dentistry occupies a leading place in promoting the services it offers. Thus, over time there have appeared numerous marketing companies specialized in this area, which propose various strategies aimed at attracting both individuals with good oral health for periodic checks and long-term health maintenance, as well as individuals in urgent need. oral rehabilitation. However, it should not be overlooked that dentistry tends to become a type of commercial medicine that often promotes aesthetic and not functional treatments. This aspect is due to the high demand for dental-facial cosmetic services, including: teeth whitening, lip augmentation, cheekbones lifting, dental facet application. The causes that have led to the increase of the requests for this type of interventions are represented by the aggressive promotion by the media sometimes of public personalities who have resorted to these interventions. Therefore, dental marketing should be applied correctly in order to increase the quality of life of the individual by ensuring good oral cavity health, with certain limitations that prevent the danger of dental functionality in the aesthetic effect. Our study aims to highlight the correct techniques for promoting a dental clinic, but also to bring to the fore the news in the field of dental medicine that contributes to the increase of the profit.